An In Vitro Analysis of Disintegration Times of Different Formulations of Olanzapine Orodispersible Tablet: A Preliminary Report - Hobbs, David (Springer International Publishing, 2013)
BACKGROUND: Orodispersible tablets (ODTs) are tablet or wafer forms of medication that disintegrate in the mouth, aided only by saliva. ODTs rely on different fast dissolve/disintegration manufacturing technologies. OBJECTIVES: Disintegration time differences for several olanzapine ODT forms were investigated. Risperdal M-Tab(®) was included as a non-olanzapine ODT comparator. RESEARCH DESIGN AND METHODS: Eleven olanzapine ODT examples and orodispersible risperidone strengths were evaluated in vitro for formulation composition, manufacturing method, disintegration and dissolution characteristics, and formulation differences in comparison with freeze dried Zydis(®) ODT. Automated dissolution test equipment captured ODT dissolution rates by measuring real-time release of active ingredient. A high-speed video camera was used to capture tablet disintegration times in warm simulated saliva. MAIN OUTCOME MEASURE: The main outcome measure was the disintegration and dissolution characteristics of the ODT formulations. RESULTS: The ODT manufacturing method was associated with time to disintegrate; the fastest were freeze dried tablets, followed by soft compressed tablets and then hard/dense tablets. Olanzapine Zydis(®) was the only ODT that completely disintegrated in less than 4 s for all strengths (5, 10, 15, and 20 mg), followed by 5-mg Prolanz FAST(®) (12 s) and then risperidone ODT 4 mg (40 s). Reasons for slow dissolution of the olanzapine generics may include low product potency, excipient binding, excipient solubility, active ingredient particle size and incomplete disintegration. CONCLUSIONS: Differences in the formulation and manufacturing process of olanzapine ODTs appear to have a strong influence on the disintegration time of the active compound; differences that may potentially impact their use in clinical practice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40268-013-0030-8) contains supplementary material, which is available to authorized users.